STRETCHING PROCESS OF PLASMID DNA MOLECULE IN OPTICAL TWEEZERS USING CW GAUSSIAN LASER BEAM - Ho, Quangquy; Trung, Thai Dinh; Luu, Mai Van; Lanh, Chu Van; Thanh, Thai Doan; Quy, Ho Quang (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
The trapping dynamics of plasmid DNA molecule linking to polystyrene microsphere (trapped bead) in optical tweezers are investigated in the CW regime using the finite difference Langevin equation (FDLE). The obtained results show that, due to the extension of DNA moleucle, the stretching process characterizing by its pulling time, and stretched length depend on the peak intensity of laser beam and its initial position. The conditions to stretch plasmid DNA molecule in stretching state are discussed and the threshold value of energy of lase beam is found out and compared to that of Î»-phage DNA moeucle